2012
DOI: 10.1002/jgt.21668
|View full text |Cite
|
Sign up to set email alerts
|

Cycle-Saturated Graphs with Minimum Number of Edges

Abstract: A graph G is called H‐saturated if it does not contain any copy of H, but for any edge e in the complement of G, the graph G+e contains some H. The minimum size of an n‐vertex H‐saturated graph is denoted by sat(n,H). We prove sat(n,Ck)=n+n/k+O((n/k2)+k2)holds for all n≥k≥3, where Ck is a cycle with length k. A graph G is H‐semisaturated if G+e contains more copies of H than G does for ∀e∈E(G¯). Let ssat (n,H) be the minimum size of an n‐vertex H‐semisaturated graph. We have ssat(n,Ck)=n+n/(2k)+O((n/k2)+k).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…Since each y ∈ S 2 is adjacent to two vertices in f (y) ∩ U 1 3 , and the vertices in S 1 satisfy (7), it follows 2|S 2 | ≤ 2|U 1 31 | + |U 1 32 | + |U 1 34 | + 3|U 1 36 |, and by (13), (6), (12), and (14),…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Since each y ∈ S 2 is adjacent to two vertices in f (y) ∩ U 1 3 , and the vertices in S 1 satisfy (7), it follows 2|S 2 | ≤ 2|U 1 31 | + |U 1 32 | + |U 1 34 | + 3|U 1 36 |, and by (13), (6), (12), and (14),…”
mentioning
confidence: 96%
“…Barefoot et al [2] showed that n + c 1 n/k ≤ sat(n, C k ) ≤ n + c 2 n/k for some positive c 1 , c 2 . They [2] and Gould, Luczak, and Schmitt [13] gave new upper bounds for sat(n, C k ) for small k. Recently, Füredi and Kim [12] gave almost exact asymptotics for sat(n, C k ) as k is fixed and n → ∞. For more results and open problems, see the excellent survey by Faudree, Faudree, and Schmitt [10].…”
mentioning
confidence: 99%
“…Johnson and Pinto [27] also study another type of saturation problem, which is often referred to as semi-saturation [18,22] (other terms have also been used: see [10,28,32,34,36]). Given graphs F and H, say that a spanning subgraph G of F is (F, H)-semi-saturated if, for every edge e ∈ E(F) \ E(G), the graph G + e contains more copies of H than G does.…”
Section: Semi-saturationmentioning
confidence: 99%
“… gave new upper bounds for sat(n,Ck) for small k . Recently, Füredi and Kim gave almost exact asymptotics for sat(n,Ck) as k is fixed and n. For more results and open problems, see the excellent survey by Faudree et al.…”
Section: Introductionmentioning
confidence: 99%